Rune Carvers and Sponsor Families on Bornholm - Kitzler Åhfeldt, Laila; Imer, Lisbeth M. (Danish Journal of Archaeology, 2019)
The runestones on Bornholm have for a long time aroused discussion due to their singular character and dating as compared to most runestones in other parts of Denmark. In this paper, the relations between sponsors and rune carvers have been investigated through analysis of the carving technique by means of the first 3D-scanning and multivariate statistical analysis ever carried out on the Danish runestone material. The results indicate that the carvers were attached to the sponsor families and that the carvers were probably members of those families. During the fieldwork, a fragment of a previously unknown runestone was documented in the church of St. Knud.